Inheritance Pattern of Some Morphological Characters in Maize (Zea mays L.): Genetic Analysis of Maize - Khan, Amanullah; Khan, Shah Jehan; Mansoor, Muhammad; Aziz, Abdul (Biological Sciences - PJSIR, 2015)